Pengaruh Penerapan Sistem E-Filling Dan Peran Relawan Pajak Dalam Meningkatkan Kepatuhan Pelaporan E-Spt WPOP Pada Masa Pandemi Covid-19 Di Wilayah Kerja KPP Pratama Bengkulu Dua - Budi Astuti; Popi Putri Prananda; Nensi Yuniarti Zs; Yudi Partama Putra; Mirra Sri Wahyuni (UNIVED Press, 2023)
This study aims to analyze the effect of implementing the e-filling system and the role of tax volunteers in improving individual taxpayer electronic annual notification reporting compliance during the Covid-19 pandemic in the KPP Pratama Bengkulu Dua working area. The research type used is a quantitative type with an associative quantitative approach. The population in this study is individual taxpayer in the work area of ​​KPP Pratama Bengkulu Dua, the number of respondents in this study is 50 people. Methods of data collection using a questionnaire. Based on the results of multiple linear regression, the regression equation form Y = 8.777 + 0.150 + 0.476. The results of the research and partial hypothesis testing show that the application of the E-Filling System has no significant effect on electronic annual notification individual taxpayer reporting compliance, the significance value is 0.321 > 0.05 and the t value is 1.002 < t table 2011, the role of Tax Volunteers has a significant effect on E reporting compliance. electronic annual notification individual taxpayer, the significance value is 0.000 < 0.05 and the f arithmetic value is 24,236 > f table 3.20, Simultaneously the E-Filling system and the role of tax volunteers have a significant effect on compliance with WPOP E-SPT reporting, the significance value is 0.000 < 0.05 and the f count 24,236 > f table 3.20